Governmental Discretion under the General Principles of Good Governance: A Normative Analysis of the Abuse of Administrative Authority in Indonesia - Diana Komena; Fitri Anita (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
Governmental discretion is an essential instrument of modern public administration, particularly when statutory law does not explicitly regulate specific circumstances. It allows public officials to respond flexibly to complex administrative situations while maintaining effective public services. This study examines governmental discretion in Indonesian administrative law, its relationship with the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AUPB), and the potential for abuse of authority in administrative decision-making. Using normative legal research, the study applies statutory, conceptual, and case approaches to analyse legislation, legal doctrines, and judicial decisions. The findings show that discretion constitutes a legitimate legal mechanism when exercised according to the purpose of delegated authority, applicable legislation, and good governance principles. However, weak administrative supervision and limited institutional understanding of its legal boundaries may result in maladministration and abuse of authority. Therefore, stronger oversight, improved legal competence among public officials, and consistent implementation of good governance principles are required to ensure accountable, transparent, and citizen-oriented public administration.